Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 1 - Section 1.6 - Properties of Integral Exponents - Exercise Set - Page 80: 114



Work Step by Step

$$(\frac{x^{6}y^{-7}}{2})^{-3}$$ Recall the power rule: $(a^{m})^{n}=a^{mn}$ Thus, $=\frac{x^{6\cdot-3}y^{-7\cdot-3}}{2^{-3}}$ $=\frac{x^{-18}y^{21}}{2^{-3}}$ Recall the negative exponent rule: $a^{−n}=\frac{1}{a^{n}}$ and $\frac{1}{a^{-n}} = a^{n}$ Thus, $=\frac{x^{-18}y^{21}}{2^{-3}}$ $=\frac{2^{3}y^{21}}{x^{18}}$ $=\frac{8y^{21}}{x^{18}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.